1982
DOI: 10.1093/ajcp/77.6.762
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Studies of Peripheral Myeloblasts and Bone Marrow Fibroblasts in Acute Myelofibrosis

Abstract: Chromosome analysis with giemsa-trypsin banding was performed on circulating myeloblasts and cultured bone marrow fibroblasts from a patient with acute myelofibrosis. Major karyotypic abnormalities were found in the myeloblasts involving chromosomes #1, 3, 5, 13, and 16; no chromosome abnormalities were detected in the fibroblasts. In addition, a pericentric inversion of number 7 was present in the circulating blasts but not the fibroblasts. Pericentric inversions have not previously been associated with acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Clinical observations also suggest a role for platelet factor 4 released from a-granules as a fibroblast mitogen pathogenetically related to the devel opment of marrow fibrosis in patients with myeloprolifer ative disorders [21]. Furthermore, various cytogenetic studies failed to demonstrate chromosomal abnormalities in fibroblasts in spite of multiple changes in hematopoiet- ic cells, corroborating the nature of a primary hemopoiet ic defect in myelofibrosis, possibly in a pluripotent cell [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical observations also suggest a role for platelet factor 4 released from a-granules as a fibroblast mitogen pathogenetically related to the devel opment of marrow fibrosis in patients with myeloprolifer ative disorders [21]. Furthermore, various cytogenetic studies failed to demonstrate chromosomal abnormalities in fibroblasts in spite of multiple changes in hematopoiet- ic cells, corroborating the nature of a primary hemopoiet ic defect in myelofibrosis, possibly in a pluripotent cell [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…How ever, in this case the abnormal karyotype was identified in the preterminal stage and it is uncertain if it was present in the bone marrow at presentation. Cytogenetic studies in myelofibrosis and megakaryoblastic leukemia have been reported by several investigators [21][22][23]42,43] and were recently reviewed by Lu et al [44], Most patients were younger than 4 years and less than 30% were older than 16 years. Approximately 40% of the 115 cases reviewed were pediatric patients with Down's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow fibroblasts obtained from patients with marrow fibrosis have a normal karyotype, while their blasts show chromosomal abnormalities [12], suggesting that cytokines secreted by leukemic cells may be responsible for the fibrosis. The important cytokines participating in marrow fibrosis are TGF-β 1 , PDGF, and bFGF.…”
Section: Discussionmentioning
confidence: 99%
“…По итогам ранее выполненных работ [8][9][10][11][12][13][14][15] в список вовлеченных в перестройки были включены хромосомы 1, 3, 7, 8, 9, 11, 13, 17, 21 и 22. Основной акцент делался на повреждения хромосом 3, 1 и 13 [9,13].…”
Section: V617funclassified
“…В тетраплоидных метафазах эта аномалия не обнаружена. Обобщенный кариотип клеток выглядел следующим образом: 46,XX, der(16)t(1;16) (q21;p13) [5]/92,XXXX [5]/46,XX [10].…”
Section: результатыunclassified